EFFECTIVENESS OF ANTI-CORRUPTION MEASURES AND KEY PRIORITIES FOR THE FUTURE IN UZBEKISTAN - Fazilov Farkhod Maratovich (International Journal of Business, Law and Political Science, 2025)
Objective: This study examines the anti-corruption reforms initiated in Uzbekistan under the leadership of President Shavkat Mirziyoyev, with a focus on institutional restructuring and policy innovation aimed at enhancing transparency and accountability. Method: The research utilizes a qualitative approach through policy analysis and discourse review of official government documents, speeches, and media reports related to the National Anti-Corruption Council's activities. Results: The findings highlight significant advancements including the establishment of specialized institutions, implementation of digital systems in procurement and public services, promotion of open land auctions, and the launch of income declaration mechanisms for public officials. Public engagement and media involvement have emerged as pivotal components in fostering a national anti-corruption culture. Novelty: The study contributes new insights into Uzbekistan’s multi-sectoral approach by integrating compliance mechanisms, regional oversight expansion, and civic participation within a centralized anti-corruption framework, positioning the country as a reform model in post-Soviet governance contexts.